THE DETERMINANT OF STUDENT’S INTENTION TO USE MOBILE LEARNING - K, .; Nurkhin, Ahmad; Arief, Sandy (PEOPLE: International Journal of Social Sciences, 2015)
Utilization of mobile devices (smartphones and tablets) in the field of learning continues to grow, include in the higher education learning. The purpose of this study was to investigate the factors that influence the student’s intention to use mobile learning with the Technology Acceptance Model (TAM) approach. The sample was Economic Education students of Semarang State University who have taken courses learning development. Extended-TAM by Huang et al. (2007); & Zhu et al., (2012) have been used to collect the data. Data analysis used path analysis to test hypothesis and analysis data. The result showed that the students have good ability to use their mobile gadget for learning purposes. In the extended-TAM frame, two primer factors (perceived usefulness and perceived ease to use) have positive effect to attitude toward using and behavioral intention to use. Other result showed external factors (perceived mobility value, perceived social interaction value and prior experience) proven have positive effect to perceived usefulness. Perceived enjoyment have significant relationship with perceived to use and attitude toward using.